2023
DOI: 10.1002/ajh.27030
|View full text |Cite
|
Sign up to set email alerts
|

Systemic complement activation influences outcomes after allogeneic hematopoietic cell transplantation: A prospective French multicenter trial

Abstract: Complement activation has shown a role in murine models of graft‐versus‐host disease (GVHD) and in endothelial complications after allogeneic hematopoietic cell transplantation (allo‐HSCT). However, its impact on post‐transplant outcomes has not been so far fully elucidated. Here, we conducted a prospective multicentric trial (NCT01520623) performing serial measurements of complement proteins, regulators, and CH50 activity for 12 weeks after allo‐HSCT in 85 patients receiving a myeloablative conditioning (MAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(113 reference statements)
1
1
0
Order By: Relevance
“…Both PA and PB showed a marked increase in CRP and IL-6 as compared to patients with uneventful course. These results indicate that systemic complement activation is involved in the pathogenesis of different complications leading to severe morbidity during HSCT, which is in accordance with a previous study ( 19 ). Recent results indicate that complement inhibition is beneficial in pediatric TA-TMA ( 18 ) indicating that complement may play a role in developing HSCT-related complications.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Both PA and PB showed a marked increase in CRP and IL-6 as compared to patients with uneventful course. These results indicate that systemic complement activation is involved in the pathogenesis of different complications leading to severe morbidity during HSCT, which is in accordance with a previous study ( 19 ). Recent results indicate that complement inhibition is beneficial in pediatric TA-TMA ( 18 ) indicating that complement may play a role in developing HSCT-related complications.…”
Section: Discussionsupporting
confidence: 93%
“…Therapeutic inhibition targeted at complement component C5, preventing C5a and C5b-9 formation, seems promising as reported in a large pediatric cohort with TA-TMA ( 18 ). Furthermore, a multi-center study has previously indicated a correlation between complement activation and outcome after HSCT ( 19 ). In this study we aimed to investigate the innate immune profile, including neutrophil and platelet activation, the cytokine network, and, in particular, the function and activation of complement in HSCT.…”
Section: Introductionmentioning
confidence: 99%